Applied mu'amalat in Islamic finance the 9th Workshop in Islamic Economics and Finance 2010 (WIEF2010), 13-14 December 2010, Lecture Hall 1, Faculty of Economics & Management, UKM - Workshop in Islamic Economics and Finance 2010 : Bangi, Selangor).; Abdul Ghafar Ismail; Noraziah Che Arshad; Universiti Kebangsaan Malaysia. Fakulti Ekonomi dan Pengurusan (Bangi : Fakulti Ekonomi dan Pengurusan, Universiti Kebangsaan Malaysia, 2010)
Contains 17 papers presented in Workshop in Islamic economics and finance 2010.
Title from first page on document.
Workshop information at container: The 9th Workshop in Islamic Economics and Finance 2010.
System requirements: Adobe Acrobat Reader.
Keywords: Finance -- Islamic countries -- Congresses; Finance -- Religious aspects -- Islam -- Congresses; Banks and banking -- Religious aspects -- Islam -- Congresses